Livestock Production and Browse use by Traditional Agro-Pastoralists in the Coastal Savannah Rangelands of Ghana - Adogla-Bessa, T.; Timpong-Jones, E.C.; Adjorlolo, L.K.; Sarkwa, F.O.; Buah, M. (PRISEBS, 2012)
The Savannah region of Ghana is the main livestock rearing area of the country and produces the bulk of the country’s meat and milk. However, nutrition of ruminant livestock is seriously limited in the dry season and during this period, fodder trees and shrubs provide the necessary supplements to poor grass availability. The study aimed at establishing the extent of utilisation of browse and their importance to livestock keepers. Browse used by pastoralists in the Dangme East and North Tongu in the Eastern Coastal Savannah rangelands were identified and ranked by means of structured questionnaire interviews with fifty-eight pastoralists. Data were analysed using Statistical Package for Social Sciences (SPSS) software. Twenty-five browse species were identified, many of them indigenous trees. Griffonia, Fagara and Millettia were ranked as the most important browses. Browse was mainly used in the dry season and for small ruminants. The ranking reflected the availability and nutritive value of browse. Livestock keepers are likely to be more interested in trees and shrubs with multiple uses including browse.
Keywords: Agro-pastoralists; browse; coastal savannah; rangelands; ruminants; utilization